The importance of the church and religious congregations for Slovenian and Norwegian migrants to the United States of America. A comparative aspect - Lea, Martha (Two Homelands, 2007)
Slovenia and Norway, both small European countries, have a history of being occupied by other forces. The first had a Catholic Church, the second a Lutheran, both with a bulk of primarily rural forefathers going to America in the nineteenth century, though with a time span of forty years in-between. It became a challenge to see which differences and similarities this situation, especially the churches, brought to the emigrants in the process. No doubt, the religion influenced their lives, Slovenian Church being more autocratic, the Norwegian democratic. Both gave support in education, charity work, social and cultural activities, but under different conditions. The positive effects are easy to spur, and the long-term Americanisation effects will need a broader perspective.